Conventional water treatment improvement through enhanced conventional and hybrid membrane processes to remove Ag, CuO and TiO2 nanoparticles mixture in surface waters - Serrão Sousa, Vânia (2021)
This study proposes, for the first time, to improve the most used process in water treatment, conventional coagulation (coagulation/flocculation/sedimentation, C/F/S), to maximally remove a mixture of engineered nanoparticles (ENPs) from surface waters. Thus, conventional coagulation enhanced with powdered activated carbon (C/F/S + PAC) and hybrid membrane treatment, integrating conventional C/F/S with ultrafiltration (C/F/S. UF), were optimised to maximise the removal of a mixture of ENPs (TiO2, CuO and Ag, 1:1:1) from surface waters. Results demonstrated that both optimized C/F/S + PAC and C/F/S. UF improved the removal of the metal-based ENPs in mixture, compared to conventional C/F/S, from hydrophilic natural waters with low and medium turbidity. In C/F/S + PAC treatment, Ag, Cu and Ti removal efficiencies were higher than 99%, and only ca. 3.0-2.9 mu g Ag/L and 2.0-2.5 mu g Cu/L were found in waters, while Ti concentrations were below the detection limit, representing a significant improvement to C/F/S performance, where in same situations the residual concentrations reached the 16 mu g/L. In this treatment, PAC acted as an adsorbent and also enhanced the settleability of the aggregates (ENPs-natural organic matter (NOM)) formed during C/F. In the C/F/S. UF, at 90% of water recovery rate, Ti and Cu removal efficiencies were approximately 100%, but ca. 5.0-7.0 mu g/L of Ag were found in the permeate water. After C/F/S, the Ti/Cu-NOM aggregates were removed by UF membranes, due to the size exclusion mechanism but, because of some Ag dissolution, the ionic Ag passed through the membrane pores. Overall, the processes optimisation to the ENPs removal did not affect their ability to remove other target compounds (turbidity, dissolved organic carbon, specific UV absorbance and aluminium).